ANALISIS PENGARUH BID-ASK SPREAD, MARKET VALUE, VARIANCE RETURN DAN DIVIDEND PAYOUT RATIO TERHADAP HOLDING PERIOD SAHAM BIASA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Farid Saiful Mustakim; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research to observe Bid-ask Spread, Market Value,Variance Return and Dividend Payout Ratio on Holding Period. The populationof this study is mining companies listed on the Stock Exchange in 2015-2017. Thesampling techniques using a purposive sampling method that generates the dataas much as 24 companies. This research uses a quantitative approach. Dataanalysis techniques using multiple linear regression analysis. The t test researchshow that Bid-Ask Spread and Market Value variable has significantly positiveeffect on the Holding Period. While Variance Return and Dividend Payout Ratiovariable has no effect on the Holding Period. The simultaneous test research (ftest) show that Bid-Ask Spread, Market Value, Variance Return dan DividendPayout Ratio variables significantly influence on Holding Period.Keywords: Holding Period, Bid-Ask Spread, Market Value, Variance Return,Dividend Payout Ratio